Secured shared authentication key with two-way clock synchronization over multiparty Quantum Communication (KIV) - Azahari, Nur Shahirah; Harun, Nur Ziadah; Ramli, Sofia Najwa; Zukarnain, Zuriati Binti Ahmad (Springer Nature, 2023)
Authentication is a security function that ensures the system’s proper security by identifying and verifying users. Despite the advantages of quantum computers, it is still difficult to enforce authentication on behalf of multiple quantum channel users without the involvement of a third party because present protocols only consider two parties involved in communication. Scalability becomes an issue as the number of parties engaged in the quantum network increases. In addition, an eavesdropper may disguise herself among numerous participants and take advantage of the circumstances to gather information. The authentication method should be used throughout the quantum data exchange process to ensure that the parties participating in the protocol are who they claim to be. The suggested protocol’s implementation has been tested using a simulation written in Python. This research aims to propose a protocol for multi party authentication procedures without the assistance of a third party. The result of the proposed protocol is expected to be a simple and reliable quantum experiment. Importantly, this protocol can establish an environment that is more secure in terms of authentication and allows numerous parties to communicate freely and openly.